Production, Expression And Characterization Of A Heat-Stable Organic Solvent Tolerant Lipase From Bacillus Sp, Strain 42 - Eltaweel, Mohamed Abdallah (2005)
Ninety two bacterial strains were isolated from oil palm effluent from Bangi,Selangor; Kluang, Johor; Alor Gajah hot spring (up to 54 OC) Melaka and Slim River hot spring (up to 9I0C) Perak. An enrichment culture technique was used to isolate bacteria utilizing olive oil as a substrate. Cultures were incubated at 60°C to select for the thermophilic bacteria. Eight isolates showed lipolytic activity on tributyrin and triolein agar plates. In order to screen for highest lipase producer, six production media were used. Isolate 42 was observed to produce the highest level (0.059 Ulml) after 72h. Its crude lipase retained its full activity when preincubated at 70°C for 30 min. It also showed high stability in several organic solvents (25% vlv). Furthermore, its activity was enhanced in benzene, hexane and hexadecane while, completely inhibited by butanol. Isolate 42 was identified as Bacillus sp. Strain 42 using 16s rDNA. The nucleotide sequence deposited at GenBank under accession number AY 7631 18. Further optimization studies were done in order to determine the best lipase production condition. lnoculum size of 3% proved to be the best for lipase production, with an optimum temperature of 50°C when, grown under shaking condition of 150 rpm. A combination of tryptone and yeast extract was the best nitrogen source. Lipase production was stimulated by olive oil. The lipase gene was amplified by polymerase chain reaction using consensus primers based on multiple aligned sequences of thermophilic genes from other thermophilic Bacillus species. Nucleotide sequence comparison shared high homology with the thermostable genes in Geobacillus sp., Bacillus stearothermophilus and Bacillus thermoleovorans. Nucleotide sequence deposited at GenBank under accession number AY 787835. The amplified gene was successfully cloned using a pQE-30 UA expression vector and induced by IPTG at the optimum concentration of 0.75 mM. The recombinant lipase was facilitated by the fusion of 6-histidine and this allowed a one-step purification of the lipase enzyme using Ni-NTA affinity chromatography. The histidine-tagged lipase was purified 6-fold with a yield of 21.7%. Purified lipase migrated as a single band with a molecular mass of -43 KDa on SDS-PAGE. The purified lipase showed high activity at 70°C with its optimum at pH 8.0. The enzyme was stable over a broad range of pH from 6.0 to 10.0. It also showed high stability with half-lives of 315 min at 60°C, 120 min at 65OC, and 45 min at 70°C. Preincubation enzyme activity was stimulated with Na+, K' and ca2+. While, zn2+, ~ n ' + and Fe *+ at high concentration (10 mM) were greatly inhibitory. Protease inhibitors Bestatin and pepstatin stimulated the lipase activity while, phenylmethylsulfonyl fluoride (PMSF) completely inhibited the lipase activity. Tween 80 (0.1%) enhanced the lipase activity while higher concentration ( I %) dramatically decreased the lipase activity. The activity of preincubated enzyme in heptanol (log P 2.4) and octanol (log P 2.9) was slightly enhanced while, remains very stable with other organic solvents tested. Solvents such as ethylbenzene (log P 3.1) and dodecane (log P 6.6) reduced the lipase activity up to 35% and 38%, respectively. The highest specificity was observed towards tricaprylin (CtJ, followed by tricaprin (Clo). Its hydrolyzed all the natural oils tested, with highest hydrolysis rate on olive oil.